2012
DOI: 10.1155/2012/168046
|View full text |Cite
|
Sign up to set email alerts
|

Superior Mesenteric Artery Dissection after Extracorporeal Shockwave Lithotripsy

Abstract: The use of shockwave lithotripsy is currently the mainstay of treatment in renal calculosis. Several complications including vessel injuries have been implied to extracorporeal shockwave lithotripsy. We report an isolated dissection of the superior mesenteric artery in a 60-year-old male presenting with abdominal pain which occurred three days after extracorporeal shockwave lithotripsy. The patient was treated conservatively and the abdominal pain subsided 24 hours later. The patient's history, the course of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…By reviewing literature, a rare case of an isolated SMA dissection after extracorporeal shockwave lithotripsy was ever reported in 2012. 4 Although the epigastric pain of our patient was already notified before extracorporeal shockwave lithotripsy performing, the pain became aggravated after urologic ward discharge.…”
Section: Discussionmentioning
confidence: 71%
“…By reviewing literature, a rare case of an isolated SMA dissection after extracorporeal shockwave lithotripsy was ever reported in 2012. 4 Although the epigastric pain of our patient was already notified before extracorporeal shockwave lithotripsy performing, the pain became aggravated after urologic ward discharge.…”
Section: Discussionmentioning
confidence: 71%
“…The etiology of spontaneous SMA dissection has not yet been established, but has been associated with atherosclerosis, cystic medial necrosis, fibromuscular dysplasia, connective tissue disorders, trauma, elastic tissue disorders (Marfan and Ehlers–Danlos syndrome), abnormal curvature of the origin of the SMA, and uncontrolled hypertension . It has been hypothesized by Solis et al that the dissection usually begins 1.5–3 cm from the orifice of the SMA, thus sparing the origin of the artery .…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on the best medication for anticoagulation. Sparks et al have suggested that indications for surgery are increasing size of the aneurysmal dilation of the SMA, luminal thrombosis, signs of intestinal ischemia, or persistent symptoms despite anticoagulation . Various procedures for surgical intervention have been reported .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations